Effect of virtual interactions through avatar agents on the joint Simon effect. - Yuki Harada; Yoshiko Arima; Mahiro Okada (PLoS ONE)
The joint Simon effect refers to inhibitory responses to spatially competing stimuli during a complementary task. This effect has been considered to be influenced by the social factors of a partner: sharing stimulus-action representation. According to this account, virtual interactions through their avatars would produce the joint Simon effect even when the partner did not physically exist in the same space because the avatars are intentional agents. To investigate this, we conducted two joint experiments in which participants controlled avatars as their agents in immersive virtual environments. In Experiment 1, participants were asked to touch a virtual button through their avatars when a target color of an object was presented. The target position was manipulated to be compatible with the button (compatible stimulus) or incompatible with the button (incompatible stimulus). In Experiment 2, the task was identical to that in Experiment 1 except that participants' gaze position was either visualized or not during the task. We hypothesized that visualizing the partner's gaze would enhance the joint Simon effect because gaze is a cue to mentalize others' internal states. The results showed that avatar-based interactions more significantly delayed responses for the incompatible than for the compatible stimulus. However, inconsistent with our hypothesis, visualizing the partner's gaze position did not influence responses for spatially competing stimuli. These results suggest that virtual interactions through avatar agents can produce the joint Simon effect even when the partner does not physically exist in the same space.